2013
DOI: 10.1101/lm.029660.112
|View full text |Cite
|
Sign up to set email alerts
|

Post-retrieval late process contributes to persistence of reactivated fear memory

Abstract: Several studies have demonstrated the mechanisms involved in memory persistence after learning. However, little is known about memory persistence after retrieval. In this study, a protein synthesis inhibitor, anisomycin, was infused into the basolateral amygdala of mice 9.5 h after retrieval of contextual conditioned fear. Anisomycin attenuated fear memory after 7 d, but not after 2 d. In contrast, infusion of anisomycin 5-or 24-h post-retrieval was ineffective. These findings indicate that anisomycin attenuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 47 publications
4
14
0
4
Order By: Relevance
“…The late reconsolidation process after retrieval in contextual fear memory has been demonstrated in at least two papers. The late reconsolidation of contextual fear memory requires protein synthesis in the BLA in mice (Nakayama et al, 2013). In our previous study, we demonstrated that cold water stress disrupted the late reconsolidation of contextual fear memory in rats (Yang et al, 2013).…”
Section: Role Of Hippocampal Ne In the Persistence Of Extinction Ltmmentioning
confidence: 99%
“…The late reconsolidation process after retrieval in contextual fear memory has been demonstrated in at least two papers. The late reconsolidation of contextual fear memory requires protein synthesis in the BLA in mice (Nakayama et al, 2013). In our previous study, we demonstrated that cold water stress disrupted the late reconsolidation of contextual fear memory in rats (Yang et al, 2013).…”
Section: Role Of Hippocampal Ne In the Persistence Of Extinction Ltmmentioning
confidence: 99%
“…Pesquisas anteriores mostraram que a AMD é uma importante estrutura encefálica envolvida na aprendizagem de memórias aversivas, e na formação e expressão de memórias emocionais através das muitas projeções para outras regiões do encéfalo que também estão envolvidas no armazenamento da informação recém-adquirida (Jerusalinsky et al, 1992;Cahill e Mcgaugh, 1998;Izquierdo et al, 1998;Ambrogi Lorenzini et al, 1999;Fanselow e Ledoux, 1999;Mcgaugh, 2004;Wilensky et al, 2006;Moscarello e Ledoux, 2014). Além disso, já foi demonstrado que a infusão de ANI na AMD de roedores prejudica tanto a consolidação quanto a reconsolidação de memórias de medo contextual (Nader;Schafe e Le Doux, 2000; Schafe e Parsons et al, 2006;Wilensky et al, 2006;Nakayama et al, 2013). Nesse sentido, nosso presente estudo corrobora com os achados anteriores que mostram que esta estrutura límbica é importante para a consolidação de memórias de esquiva inibitória .…”
Section: Discussionunclassified
“…Esta pode durar minutos a dias, e sofre uma transição de um estado lábil para um fixo. Durante o período de consolidação, para que a informação recém-aprendida durante a fase de aquisição seja transformada em modificações estáveis, é necessário que ocorra síntese proteica (Nakayama et al, 2013). A evocação ocorre quando o animal retorna ao mesmo contexto onde houve o pareamento com o estímulo aversivo (Abel e Lattal, 2001).…”
Section: Introdução Memóriaunclassified
See 2 more Smart Citations